PENGARUH LARUTAN SODIUM HIPOKLORIT TERHADAP KEKUATAN TRANSVERSAL PADA BAHAN BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS - Dharma Satya Aprianto; Zullia Taftyanti (Lembaga Penelitian Universitas YARSI, 2015)
Among various ways to clean the denture based material is by its immersion in disinfectant solution, such as sodium hypochlorite. Heat polymerized acrylic is denture based material that is easily broken because of its low transverse strength. This study was aimed to observe the transverse strength of denture based material heat polymerized acrylic resin after immersion in sodium hypochlorite. This research used 24 samples of heat cured acrylic resin plates measuring 65 mm long, 10 mm wide and 2.5 mm thick. The samples being divided into 4 groups were immersed in sodium hypochlorite 1% and water for 8 hours and 24 hours in 7 days. The transverse strength of acrylic plate were then tested using universal testing machine. The measurement results were statistically analyzed employing “one way ANOVA”. The result showed no significant changes on transverse strength of heat-cured acrylic plate. It was concluded that sodium hypochlorite solution did not provide any significant changes in the transverse strength of heat cured acrylic resin.